2013
DOI: 10.1111/tri.12122
|View full text |Cite
|
Sign up to set email alerts
|

Induction therapy in pancreas transplantation

Abstract: Summary Induction therapy, the initial high‐dose bolus of immunosuppression given perioperatively to transplant patients, is almost ubiquitous in pancreas transplantation. Despite the frequent use, scientific data on the risks and benefits of induction therapy are scarce, especially as it concerns use specifically for pancreas transplantation. Indeed, none of the currently used induction agents are approved as induction therapy for pancreas transplantation, yet potential benefit is largely extrapolated from tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 31 publications
0
25
0
2
Order By: Relevance
“…This may support the use of induction therapies (IT), a standard protocol worldwide [6,18]. However, it has not been demonstrated that there is a clear benefit (any drug over another) on long-term outcomes or even that these auto-antibodies may play a role in outcomes [17,18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may support the use of induction therapies (IT), a standard protocol worldwide [6,18]. However, it has not been demonstrated that there is a clear benefit (any drug over another) on long-term outcomes or even that these auto-antibodies may play a role in outcomes [17,18].…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown how pancreas transplantation may induce higher rates of rejection early after transplantation compared with liver or kidney transplantation alone (KTA) [17]. There are some articles in which it is suggested that autoantibodies (anti-GAD mainly) may be related at least in part with this phenomena.…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence immunosuppressive practice has reflected practice in other areas of organ transplantation, with an additional effort to avoid prolonged steroid administration. Avoidance of steroids has been facilitated in part by the use of induction therapy, a short period of high dose immunosuppression in the peri-operative period, often characterised by the use of lymphocyte depleting antibodies [83].…”
Section: Immunosuppression For Pancreas Transplantationmentioning
confidence: 99%
“…The majority of units use biological induction (thymoglobulin, alemtuzumab, or basiliximab) followed by a combination of tacrolimus and mycophenolate, and the use of steroids is advocated by some but not all units. There is no conclusive evidence regarding optimal induction therapy; single center studies are small, and of the two multicenter trials, the largest examined an agent (daclizumab) that is no longer available, and the other used variable induction agents (Niederhaus et al 2013). The use of non-nephrotoxic medication is attractive, but experience in the use of sirolimus following pancreas transplantation remains limited (Kandula et al 2012).…”
Section: Immunosuppressionmentioning
confidence: 99%